Superconducting diode effect sign change in epitaxial Al-InAs Josephson junctions - Neda Lotfizadeh; William F. Schiela; Barış Pekerten; Peng Yu; Bassel Heiba Elfeky; William M. Strickland; Alex Matos-Abiague; Javad Shabani (Communications Physics, 2024)
Abstract There has recently been a surge of interest in studying the superconducting diode effect (SDE) partly due to the possibility of uncovering the intrinsic properties of a material system. A change of sign of the SDE at finite magnetic field has previously been attributed to different mechanisms. Here, we observe the SDE in epitaxial Al-InAs Josephson junctions with strong Rashba spin-orbit coupling (SOC). We show that this effect strongly depends on the orientation of the in-plane magnetic field. In the presence of a strong magnetic field, we observe a change of sign in the SDE. Simulation and measurement of supercurrent suggest that depending on the superconducting widths, W S, this sign change may not necessarily be related to 0–π or topological transitions. We find that the strongest sign change in junctions with narrow W S is consistent with SOC-induced asymmetry of the critical current under magnetic-field inversion, while in wider W S, the sign reversal could be related to 0–π transitions and topological superconductivity.